Isolated diplopia and gaze limitation following blunt maxillary trauma in a child: a pediatric orbital floor fracture with muscle entrapment - Burak Demirci; Abuzer Coşkun; Şakir Ömür Hıncal; Halil Can Doğan; Selman Gündoğan (Izmir Katip Celebi University Faculty of Medicine, 2026)
Maxillofacial trauma may be associated with orbital wall fractures and isolated ocular movement disorders. Careful ocular examination in the emergency department is essential for early diagnosis. A 14-year-old male presented approximately 2 hours after a punch to the right maxillary region with complaints of diplopia. Physical examination revealed limitation of upward gaze in the right eye. Orbital computed tomography demonstrated a fracture of the right inferior orbital wall, and magnetic resonance imaging confirmed entrapment of the inferior rectus muscle into the maxillary sinus. Surgical intervention was performed within 48 hours after diagnosis, resulting in full recovery of ocular motility. Orbital floor fractures in pediatric patients may present with minimal external findings but significant ocular motility impairment. Early recognition and appropriate management can prevent permanent complications.